2016
DOI: 10.1017/s1431927616011958
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Localization of Intracellular Calcium During Spermatogenesis of Sterlet (Acipenser ruthenus)

Abstract: Calcium regulates many intracellular events such as growth and differentiation during different stages of gamete development. The aim of this study was to localize and quantify the intracellular distribution of calcium during different developmental stages of spermatogenesis in sterlet, Acipenser ruthenus, using a combined oxalate-pyroantimonate technique. The distribution of calcium was described in spermatogonium, spermatocyte, spermatid, and spermatozoon stages. In the spermatogonium and spermatocyte, calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 41 publications
(55 reference statements)
2
9
0
1
Order By: Relevance
“…While most calcium is deposited in limited areas during the spermatogonium and spermatocyte stages, it is mostly detected as unbound pools (free calcium) which were released from dense isolated deposits of earlier stages of spermatogenesis and distributed in larger areas of the spermatid and the spermatozoon particularly nucleus. Similar changes in the ultrastructural distribution of calcium were observed during spermatogenesis of sterlet, Acipencer ruthenus (Golpour et al, ).…”
Section: Discussionsupporting
confidence: 65%
“…While most calcium is deposited in limited areas during the spermatogonium and spermatocyte stages, it is mostly detected as unbound pools (free calcium) which were released from dense isolated deposits of earlier stages of spermatogenesis and distributed in larger areas of the spermatid and the spermatozoon particularly nucleus. Similar changes in the ultrastructural distribution of calcium were observed during spermatogenesis of sterlet, Acipencer ruthenus (Golpour et al, ).…”
Section: Discussionsupporting
confidence: 65%
“…Only preliminary results dealing with gonadal development in cultured sterlet have been published previously (Jackson et al., ). Moreover, study on annual gonadal cycle and changes in serum sex steroid profile of fish is crucial to examine germline development and spawning pattern in fish (Barcellos et al., ; Golpour, Pšenička, & Niksirat, ; Lee & Yang, ; Manosroi, Meng‐Umphan, & Manosroi, ; Tan‐Fermin, Ijiri, Ueda, Adachi, & Yamauchi, ). Gametogenesis and gonadal cycles were evaluated in cultured male and female of white sturgeon, Acipenser transmontanus (Doroshov, Moberg, & Van Eenennaam, ), female siberian sturgeon, Acipenser baerii (Williot, Brun, Rouault, & Rooryck, ), male and female of amur sturgeon, Acipenser schrenckii (Qu, Sun, Wan, & Ma, ), and both sexes of shortnose sturgeon, Acipenser brevirostrum (Colombo, Garvey, & Wills, ; Flynn & Benfey, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, study on annual gonadal cycle and changes in serum sex steroidprofileoffishiscrucialtoexaminegermlinedevelopmentand spawning pattern in fish (Barcellos etal., 2001;Golpour, Pšenička, & Niksirat, 2016b;Lee & Yang, 2002;Manosroi, Meng-Umphan, & Manosroi, 2003;Tan-Fermin, Ijiri, Ueda, Adachi, &Yamauchi, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The head of sperm (<2 μm in width) in Waigieu seaperch was bigger than that of yellow croaker (<1.6 μm in width) (Le et al ) and filefish (<1.4 μm in width) (Le et al ), but smaller than that in other teleost fishes (from 2 to 4 μm in width) (Jamieson ). Additionally, the sperm has the kidney shape that is similar to Mediterranean rainbow wrasse, Coris julis (Jamieson ), and yellow croaker (Le et al ), but is different from other teleost fish such as ball‐shaped in northern pike, Esox lucius; ovoid‐shaped in cardinal fish, Apgon imberbis ; banana‐shaped in Atlantic eel, Anguilla anguilla (Jamieson ); horse‐shoe‐shaped in filefish (Le et al ); and elongated in sturgeon (Golpour et al ). Alavi et al () reported the changes in sperm morphological and ultrastructural parameters in the freshwater species Barbus barbus during the spawning season.…”
Section: Discussionmentioning
confidence: 99%